Information and communication technologies in the education of students in elective disciplines (modules) in physical culture and sports at a university - M. V. Katrenko; Yu. A. Filippov; V. P. Chicherin; A. N. Prodius (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. The possibility of using information and communication technologies in the education of students is considered as an option to solve the problem of involving students in the educational process in physical education and maintaining their interest in learning, self-education and self-development.Goal. Studying the maximum use of information and communication technologies by students studying on an individual plan in mastering elective disciplines (modules) in physical culture and sports.Materials and methods. The study used the analysis of literary sources, online survey, online testing, and comparative data analysis.Results and discussion. In the course of the work, the importance of information and communication technologies in the educational processes of university students was established. It has been determined that knowledge of the latest technologies and the use of teaching resources is becoming an increasingly necessary condition for studying higher education disciplines. The positive impact of information educational content based on the modular principle on students performing independent work on sections of an individual plan was analyzed and confirmed. The tasks of increasing the physical capabilities of the body have been solved, as a result of adequately assessing the results of activities and making adjustments to the planning of further prospects to achieve the intended goals.Conclusion. It is concluded that the use of information and communication technologies in the implementation of physical education for students at a university helps to increase physical activity, search for new knowledge, and self-education.